The Hypoxia Training as a New Therapeutic Modality in the Treatment of Neurological Disorders - A Literature Review - Hudzińska, Patrycja; Łabuś, Małgorzata; Sieńko, Antoni; Sadowski, Jakub; Papież, Łukasz Stanisław; Krzykawski, Karol; Dołęga, Julia; Zabawa, Bartłomiej; Mól, Piotr; Maciejczyk, Tomasz (Journal of Education, Health and Sport, 2025)
Introduction: Hypoxia training has emerged as a promising therapeutic approach for various neurological disorders. This systematic review examines the neuroprotective mechanisms and potential clinical applications of hypoxic training in neurology. Materials and Methods: Literature review was conducted using databases such as PubMed, NCBI, and Google Scholar, with search terms including "hypoxia", "hypoxia training", "neuroprotection", "neurological disorders" and "physical activity". State of knowledge: Controlled exposure to moderate hypoxia induces beneficial cellular and molecular adaptations in the nervous system. Key mechanisms include HIF-1 pathway activation, enhanced antioxidant responses, increased neuroplasticity, and serotonergic system modulation. These adaptations protect neurons against oxidative stress, excitotoxicity, and mitochondrial damage. Hypoxia training shows promise in treating neurodegenerative diseases, stroke, and spinal cord injury, improving cognitive, motor, and respiratory functions. Optimal protocols involve 10-16% oxygen exposure for 30-240 minutes, 3-7 times weekly for 2-6 weeks. Conclusions: Hypoxia training offers a potential non-pharmacological approach to treating neurological disorders with minimal side effects when properly administered. Further research is needed to establish optimal protocols, identify novel biomarkers, and conduct larger clinical trials to fully understand its therapeutic potential in neurology.